The influence of leadership role modeling, work-life balance, and the spirit of collaboration on on lecturers' professional commitment: - - Zainuri, Zainuri; Setyaningsih, Sri; Herfina, Herfina (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The purpose of this study was to determine the impact of three factors, leadhersip role modeling, work-life balance, and a spirit of collaboration on lecturers' professional commitment. To achieve this objective, a descriptive survey was conducted, using Cresswell's (2018) descriptive survey theory. Data were collected through a questionnaire, and the results are presented as percentages to provide a clear and straightforward depiction of the findings. This approach allowed for a systematic understanding of the factors influencing professional commitment within the context of higher education. The study was conducted with a sample of 15 permanent lecturers, representing six faculties at Pancasila University. The research was carried out during January 2024, providing a snapshot of the current perceptions of faculty members. These subjects were selected to provide insight into the specific dynamics at Pancasila University, which may reflect broader trends in academic institutions. By focusing on a relatively small sample, this study aimed to provide in-depth, detailed insights into the personal and professional factors influencing lecturers’ commitment to their work. The data analysis began by determining the ideal score for each variable and measuring the level of lecturers' perceptions using a percentage formula. This method helped to quantify the perceived impact of leadership, work-life balance, and collaboration on lecturers' professional commitment. The results indicated that exemplary leadership and a collaborative environment had the most significant influence on lecturers' motivation, job satisfaction, and commitment to the institution. Work-life balance was also found to positively affect professional commitment, but to a lesser extent compared to leadership and collaboration. In conclusion, this study emphasizes the importance of leadership, work-life balance, and a spirit of togetherness in strengthening lecturers' professional commitment. The findings suggest that universities should invest in leadership development, foster a collaborative academic environment, and support work-life balance initiatives to enhance faculty engagement and retention. Future research could expand the sample size and examine additional factors that may contribute to professional commitment in higher education settings.